Implementasi Kebijakan Penyelenggaraan Pendidikan Profesi Guru oleh Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta - Wahyu Handayani; Khaerul Umam Noer (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
The disparity in the number of certified teachers remains a critical issue that must be addressed to reduce the prevalence of non-certified educators. This challenge is further compounded by the limited availability of certification quotas relative to the number of teacher graduates. The Teacher Professional Education (PPG) program, issued by the Directorate General of Teachers and Education Personnel (Ditjen GTK), has undergone regulatory changes based on Ministerial Regulation No. 19 of 2024, focusing on prospective teachers and specific in-service teachers. The PPG program aims to reduce the number of non-certified teachers and equip future educators with theoretical and practical competencies for application in schools.This study aims to examine the implementation of the PPG policy by the Faculty of Education, Universitas of Muhammadiyah Jakarta. Utilizing Edward III’s implementation model—covering communication, resources, disposition, and bureaucratic structure—a qualitative descriptive approach was employed.The findings reveal that the Faculty has effectively communicated the PPG program to prospective teachers. However, the Department of Education and Culture of South Tangerang (Dikbud Tangsel) has not fully disseminated this information to in service teachers, many of whom lack understanding of the administrative selection procedures. Both FIP and Dikbud Tangsel face limitations in human resource capacity. Furthermore, each institution operates within defined areas of authority—FIP as the organizer of the PPG. Nonetheless, both have carried out their roles in accordance with the SOPs issued by Ditjen GTK, while adhering to their respective mandates.